PENGARUH PARTISIPASI ANGGARAN DAN PENEKANAN ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN ASIMETRI INFORMASI SEBAGAI VARIABEL INTERVENING PADA RUMAH SAKIT SUMBERGLAGAH MOJOKERTO - jurnalpps pps; Dwi Lina Nur Wiyastuti; Indra Prasetyo; C. Sri Hartati (Jurnal Manajerial Bisnis, 2021)
This research aims to examine and to analyze the influence of budget participation and budgeting emphases toward budgetary slack throught asymmetric information as intervent variable in Sumberglagah Hospital Mojokerto. This research used quantitative method with 50 respondents. This research use purposive sampling. The data used through quitionarre in each unit which are head of subunit, unit coordinate, and the chair of room in Sumberglagah Hospital Mojokerto. The quetionarre result managed PLS (Partial Least Square). The result shows that budget participation and budget emphasis have positive significant effect to asymmetric information, budgeting participation have non significant effect toward budgeting slack, budget emphasis and asymmetric information have positive significant effect to budgetary slack. Meanwhile, budget participation and budget emphasis have non significant effect toward budgetary slack throught asymmetric information. Keywords: budget participation, budget emphasis, information asymmetry, budgetary slack.